Modeling tourist's mode choice behavior under parking and cordon charge policies - Azari, Kian Ahmadi; Arintono, Sulistyo; Hamid, Hussain (IEEE, 2011)
Traffic congestion is a perennial problem at seasonal tourist destinations throughout the world. Meanwhile, understanding the mode choices of tourist's traveler will help to identify effective solutions. This analysis contributes to that effort by characterizing the mode preferences of tourists under parking and cordon polices in central business district (CBD) of Mashhad city. With respect to the research methodology, this research employs econometric model, discrete choice model. Using a stated preference survey of visitors, the results presented that travel time, parking fare, cordon cost, education levels and vehicle price type are characteristics in Mashhad city that determine tourist's modal choice and influence the modal shift from congestion pricing in central business area. In addition, the finding shows that congestion pricing has more effective response than the parking strategy.